The Appearance of False Sign in Ads at Social Media - Ilhamsyah Ilhamsyah; Herlina Herlina (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2016)
The aim of this study is to determine the presence of signs and combinations ofsigns (codes) that are present on the fictitious figure of Sarah Aprilia in Cologne Baskadvertising  on  the  internet.  The  sign  and  the  code  in  general  should  have  a  commonunderstanding by prospective readers (target audience). This research used qualitativeapproach  with  interpretative  descriptive  method  because  semiotic  science  is  diggingand discovery the meaning. In analyzing the fictitious figure of Sarah Aprilia, the signthat  appearance  is  false  sign.  Deceptive  mark  is  a  sign  that  unknown  origin  ,  but  theengineering rests on a natural object (hybrid), but viewers assume it was real presence.This is due to the many cross signs presented visual codes that make the figure of SarahAprilia as a real figure.